Ragam Pendekatan dalam Pengembangan Kurikulum Pendidikan Agama Islam (PAI) - Muhamad Ghazali Abdah (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2019)
The curriculum is an inseparable part of an education system, because it is one component in determining the achievement of a goal. Likewise the Islamic religious education curriculum (PAI) also has a very central role in various educational processes in order to achieve the direction and purpose of Islamic education itself. Islamic education aims to develop all the potential that humans have based on the Shari'ah of Islam. However, the PAI curriculum in fact, still holds problems in life, for example the learning model is still dogmatic, repository and overlapping, and the religious concepts taught have no relevance in life in modern times today. Educators and all education staff are required to truly be able to understand the curriculum and be able to develop it. In developing an Islamic religious education curriculum (PAI) certain approaches are needed, so that the curriculum developed can lead students towards the desired changes. Educators can choose a number of approaches that are appropriate to their learning model and of course by paying attention to the characteristics of Islamic religious education itself. Among the approaches that can be used in curriculum development there are four, namely: academic, humanistic, technological and social reconstruction approaches. The developed curriculum can later be implemented by various PAI teachers in the teaching and learning process in schools.